2020
DOI: 10.1021/acs.jced.9b00798
|View full text |Cite
|
Sign up to set email alerts
|

Solution Thermodynamics for the Thorium Complexation with N-(2-Hydroxyethyl) Iminodiacetic Acid

Abstract: N-(2-Hydroxyethyl)iminodiacetic acid (HEIDA-H 2 ) is one of the major chelating agents present in the mixed nuclear waste of the Hanford site. The complexation of thorium with HEIDA-H 2 in aqueous medium was investigated to understand the capability of HEIDA-H 2 to affect the migration of actinides from the waste storage sites. The present studies aimed at determining the thermodynamic parameters of Th(IV)−HEIDA complexes to know the speciation, stability (log K) and strength of bond formations (enthalpy and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…The protonation of carboxylates is mainly driven by entropy with a very small contribution from enthalpy. The enthalpy and entropy changes for the first protonation are in agreement with the protonation of amine N, while the second protonation is in line with that of the carboxylate group …”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The protonation of carboxylates is mainly driven by entropy with a very small contribution from enthalpy. The enthalpy and entropy changes for the first protonation are in agreement with the protonation of amine N, while the second protonation is in line with that of the carboxylate group …”
Section: Resultssupporting
confidence: 69%
“…Generally, the log K P values of aliphatic acids are around 4–5, However, for ADA, the electron-withdrawing effect of quaternary amine N as well as hydrogen-bonding interactions of quarternary amine H with carboxylate increases the acidity of carboxylic groups and decreases the log K P2 and log K P3 values to 2.09 and 1.04, respectively (Figure b,c). Among the other similar derivatives, viz., iminodiacetic acid (IDA), having hydrogen on amine N, and HEIDA, having the 2-hydroxyethyl functionality on amine N, the log K P1 values are in the order IDA > HEIDA > ADA, i.e., 9.29, 8.63, and 6.69, respectively. , The trend of log K P1 confirmed that the basicity of amine N is in the order IDA > HEIDA > ADA. The electron-withdrawing inductive effect of the substituent present on amine N reduces the charge density on the N atom and therefore lowers the basicity of amine.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The chemical nature of the participating ligand and the geometry arrived by its coordination on the equatorial plane has phenomenal effects on the intensities and positions of electronic transitions of the uranyl ion in the range of 380–480 nm arising from vibronic perturbed electronic transitions. , The protonation process is an inseparable mechanism while studying the complexation phenomenon, especially with the protonated/deprotonated ligands; and the protonation thermodynamic data are a prerequisite to obtain the complexation thermodynamics data. The present studies utilized the protonation data from our previous work .…”
Section: Resultsmentioning
confidence: 99%
“…All three phosphonocarboxylic acids have three dissociable protons (two on the phosphonate group and one on the carboxylate group). Oxygen atoms present in both the groups (phosphates and carboxylates) are hard donors and could bind with most of the metal ions to form stable minerals and complexes in solid as well as solution states. , The extent of protonation and deprotonation plays a crucial role in the interaction of the metal ion with organic moieties having dissociable protons. Further, the complexation phenomenon is accompanied by the deprotonation of these ligands. Thus, the determination of the thermodynamic stability (as Δ G /log K ) and energetic balance (as Δ H and Δ S ) is a prerequisite for studying the metal–ligand interactions.…”
Section: Introductionmentioning
confidence: 99%